Sternotomy or thoracotomy for neonatal repair of coarctation of the aorta with aortic arch hypoplasiaCentral MessagePerspective - Peter Chiu, MD, MS; Addison Gearhart, MD; Ajami Gikandi, BA; Supreet Marathe, MD; Margaret Holland, PA-C; Shinichi Goto, MD; Sunil J. Ghelani, MD; Aditya K. Kaza, MD (JTCVS Open)
Objective: For neonatal repair of coarctation of the aorta, patients may either undergo thoracotomy with extended end-to-end anastomosis or sternotomy for aortic arch reconstruction with cardiopulmonary bypass. The objective of this study was to evaluate the comparative effectiveness of the 2 approaches in patients with arch hypoplasia. Methods: This is a single-center retrospective cohort study from July 2005 through May 2022 of patients who underwent neonatal repair for isolated coarctation of the aorta with additional arch hypoplasia. Inverse probability of treatment weighting is a statistical method for creating comparable pseudopopulations and was used to account for baseline differences in population. The primary outcome was aortic reintervention, and secondary outcomes were vocal cord dysfunction, length of stay, chylothorax, and phrenic nerve palsy. Results: There were 130 patients who met inclusion criteria. After weighting, the interaction between distal transverse arch size and operative approach (sternotomy vs thoracotomy) was statistically significant, P < .05 for interaction. Among patients with a distal arch z-score <−3.5, patients undergoing thoracotomy with extended end-to-end anastomosis had an increased hazard for reintervention. Sternotomy was associated with an increased length of stay in the intensive care unit by 4.7 days, P < .001, and odds of vocal cord dysfunction were also greater, odds ratio 7.1 (95% confidence interval, 1.66 to 41.26; P = .01). Conclusions: Among patients with a distal arch z-score smaller than −3.5, the hazard of reintervention was increased for patients undergoing thoracotomy with extended end-to-end anastomosis. However, length of stay and risk of vocal cord paresis was reduced in patients undergoing thoracotomy.